How to grill everything : simple recipes for great flame-cooked food - Bittman, Mark (Houghton Mifflin Harcourt, 2018)
"The ultimate grilling guide and the latest in Mark Bittman's acclaimed How to Cook Everything series. Here's how to grill absolutely everything--from the perfect steak to cedar-plank salmon to pizza--explained in Mark Bittman's trademark simple, straightforward style. Featuring more than 250 recipes and hundreds of variations, plus Bittman's practical advice on all the grilling basics, this book is an exploration of the grill's nearly endless possibilities. Recipes cover every part of the meal, including appetizers, seafood, meat and poultry, vegetables (including vegetarian mains), and even desserts. Plenty of quick, high-heat recipes will get dinner on the table in short order (Spanish-Style Garlic Shrimp, Green Chile Cheeseburgers); low and slow "project" recipes (Texas-Style Smoked Brisket, Pulled Pork with Lexington BBQ Sauce) are ideal for leisurely weekend cookouts. You'll also find unexpected grilled treats like avocado, watermelon, or pound cake, and innovative surprises--like how to cook paella or bake a whole loaf of bread on the grill--to get the most out of every fire"--